DOI: 10.31274/rtd-180817-88
|View full text |Cite
|
Sign up to set email alerts
|

Traffic grooming and wavelength conversion in optical networks

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely affect reproduction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Earlier work on WDM grooming networks concentrate on performance analysis of fixed-path (shortest-path) rout ing strategies with random wavelength assignment [27]. However, there has been very little or no significant research can be found in the literature on dynamic routing in WDM grooming networks.…”
Section: Prior Work In Connection Establishment In Wdm Grooming Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work on WDM grooming networks concentrate on performance analysis of fixed-path (shortest-path) rout ing strategies with random wavelength assignment [27]. However, there has been very little or no significant research can be found in the literature on dynamic routing in WDM grooming networks.…”
Section: Prior Work In Connection Establishment In Wdm Grooming Networkmentioning
confidence: 99%
“…Analytical models that account for dynamic routing based on up-to-date network status are complex, hence have received very little attention [26]. Analytical model for WDM/TDM networks can be found in [9,27].…”
Section: Issues and Motivationmentioning
confidence: 99%